The timing of pay - Parsons, Christopher A.; Van Wesep, Edward D. (Journal of Financial Economics, 2013)
There exists large and persistent variation in not only how, but when employees are paid, a fact unexplained by existing theory. This paper develops a simple model of optimal pay timing for firms. When workers have self-control problems, they under-save and experience volatile consumption between paychecks. Thus, pay whose delivery matches the timing of workers' consumption needs will reduce wage costs. The model also explains why pay timing should be regulated (as it is in practice): although the worker benefits from a timing profile that smoothes her consumption, her lack of self-control induces her to attempt to undo the arrangement, either by renegotiating with her employer or by taking out payday loans. Regulation of pay timing and consumer borrowing is required to counter these efforts, helping the worker help herself.